Study the Effect of Tool Geometry on Material Flow Behavior in Ti6AL4 Titanium Alloy Friction Welding Process Using CATIA V5 - هترة علي (Latakia University Journal -Engineering Sciences Series, 2021)
In order to improve material flow behavior during friction stir welding and avoid root flows of weld, a tool with a half-screw pin and a tool with a tapered-flute pin are suggested. The effect of flute geometry in tool pins on material flow velocity is investigated by the software CATIA V5. Numerical simulation results show that high material flow velocity appears near the rotational tool and material flow velocity rapidly decreases with the increase of distance away from the axis of the tool. Maximum material flow velocity by the tool with the tapered-flute pin appears at the beginning position of flute and the velocity decreases with the increase of flow length in flute. From the view of increasing the flow velocity of material near the bottom of the workpiece or in the middle of workpiece, the tool with the half-screw pin and the tool with the tapered-flute pin are both better than the conventional tool